SIMBOL KEBO SEBAGAI SARANA UPACARA DEWA YADNYA DI PURA GUNUNG PANGSUNG KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Sujana, I Made Putu (Widya Sandhi, 2019)
This study aims to conduct a study of the implementation of the dewa yadnya (ceremony for God) which uses symbol of kebo as a means of upbringing on the pujawali (ceremony) in Gunung Pangsung Temple, Labuapi District, West Lombok Regency. This research was designed in the form of qualitative descriptive research with the presentation of data in the form of words, sentences, opinions, and the like in order to find answers to the formulated problem. The focus of this research is to examine the form, function, and meaning of the implementation of the dewa yadnya (ceremony for God) which uses the kebo symbol as a means of upakara. Based on data and data analysis, this study found that the form of performing the ceremony of dewa yadnya (ceremony for God) using kebo animal as a symbol of ceremonial means in Gunung Pangsung Temple represented a belief system of Hindus by using symbolic forms in accordance with religious conditions inherited from ancestors in the past. This is as part of the realization of sradha and bhakti in order to improve the quality of their lives in this world. The function of performing the ceremony of the dewa yadnya that uses kebo as a symbol of the ceremony facilities at Gunung Pangsung Temple involves religious functions related to the implementation of beliefs, social togetherness functions to establish togetherness and the function of cultural preservation to continue the cultural traditions of the ancestral heritage. The meaning contained in the implementation of the ceremony of the dewa yadnya which uses kebo as a symbol of ceremonial means at Gunung Pangsung Temple concerns the meaning of increasing religious awareness, togetherness in performing rituals, and passing on the noble cultural values ​​of the past in order to improve the quality of their lives. Based on the above results, the implementation of dewa yadnya that uses the kebo symbol is very important as a medium for implementing Hindu beliefs in order to improve the quality of life needs to be preserved because it can bring togetherness in the father's rules that can create harmony among Hindus and contain elements of preservation cultural heritage of ancestors